Access to public information: comparative study of Poland and United Kingdom - Pieniążek, Patryk (Studia Iuridica Toruniensia, 2025)
Access to public information is currently one of the most important issues related to the functioning of a democratic state under the rule of law. This right entitles everyone to participate consciously in the social and political life of the country. It is therefore a tool of social control through which every citizen has the right to obtain information about the activities of public authorities and persons performing public functions. This article aims to present the operation of the right of access to public information in the UK and Poland, taking into account the legal arrangements that shape the way in which citizens can exercise this fundamental right in both countries.